2020
DOI: 10.3390/atmos11090934
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint Sustainability as a Tool to Address Climate Change in the Wine Sector: A Methodological Approach Applied to a Portuguese Case Study

Abstract: In the Mediterranean region, climate change is likely to generate an increase in water demand and the deterioration of its quality. The adoption of precision viticulture and the best available techniques aiming at sustainable production, minimizing the impact on natural resources and reducing production costs, has therefore been a goal of winegrowers. In this work, the water footprint (WFP) in the wine sector was evaluated, from the vineyard to the bottle, through the implementation of a methodology based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…Regarding direct water footprint, it ranged from 366 to 899 L/0.75 L bottle. The study revealed that although more than 97.5% of the water footprint was associated with vineyards, the winery stage was responsible for more than 75% of the global warming potential indicator [41]. Due to climate change projections for DDR that reveal warming and drying trends for the upcoming decades, a yield decrease is expected.…”
Section: Practices For Water Reuse and Reduction Of Water Usementioning
confidence: 99%
“…Regarding direct water footprint, it ranged from 366 to 899 L/0.75 L bottle. The study revealed that although more than 97.5% of the water footprint was associated with vineyards, the winery stage was responsible for more than 75% of the global warming potential indicator [41]. Due to climate change projections for DDR that reveal warming and drying trends for the upcoming decades, a yield decrease is expected.…”
Section: Practices For Water Reuse and Reduction Of Water Usementioning
confidence: 99%
“…16 So far the impact that the food industry has on the environment was analyzed through life cycle analysis. 17,18 However, this downstream approach makes it possible to calculate the emissions and the consumption of resources in relation to a given process, providing information on the most impactful transformation steps, without allowing for optimizing the operative conditions of the process. Mathematical simulation and optimization models provide, instead, a common way to re-design or optimize the water-energy consumption system while maintaining the highest level of food security.…”
Section: Water-food-energy Nexus and Data Reconciliation Methodsmentioning
confidence: 99%
“…Between 2015 and 2017, the total natural gas consumption was between 3204. 18 In the bottling center, the natural gas consumption shows a similar overall trend from year to year and it is mainly related to steam generation. There is a constant background consumption due to the production process, continuous along the year, to which a further consumption due to the heating of offices and plants is added in the winter period.…”
Section: Energy Consumption and Inefficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA allows us to compare different systems, products, and processes regarding the production and self-usage of energy and the extraction of the raw materials included in various treatment unit combinations [4] to find the best process scenario available [5]. Since the 1990s, different WWT topics have been examined in several previous LCA studies [6]: plant modifications and operations [7][8][9][10][11][12], modeling [13][14][15][16][17][18][19], sludge processes [11,[20][21][22], greenhouse gas (GHG) emissions [4,23,24], rainfall impact [6,25], and uncertainty [5,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%